Intergovernmental Coordination without the Big Polluters: A Recent Study - Jan-Erik Lane (Research Aspects in Arts and Social Studies Vol. 2, 2022)
Foreign policy is driven by expectations. As long as the big polluters expect few changes in the short run, they pay lip service to the theory of global warming. According to new DNA analysis, contemporary homo sapiens have been around for over 100,000 years. And this race has expanded to an astounding 8 billion people, dominating all other species and putting the other human races under its control. The 21st century may end the fantastic story about Cro-Magnons as planet Earth no longer may support advanced forms of life, i.e. low tem- perature, supply of food, access to drinking water as well as absence of war between or within nations and even civilisations. Only intergovernmental coordination can slow the process of climate change, but the nature of international relations prohibits it. The energy intensity has presented apparent changes, the extra energy for COVID-19 fighting is non-negligible for stabilising energy demand, and the energy recovery in different regions presents significant differences. A crucial issue has been to allocate and find energy-related emerging opportunities for the post pandemics.